Experiences of formal caregivers of elderly inpatients with physical disabilities in China: a qualitative study - Li-li Sun; Li Zheng; Liu-liu Chen; Zhao-di Wang; Qian Li; Li Liu (BMC, 2024)
Abstract Aim To explore the views and experiences of formal caregivers caring for older inpatients with physical disabilities. Methods It was a qualitative phenomenological study. Using purposive sampling, twelve formal caregivers were chosen in a tertiary comprehensive hospital in Hangzhou, China. Semi-structured, face-to-face interviews were conducted, guided by open-ended questions that focused on gaining rich insights into participants' views and experiences. Coding reliability thematic analysis was used to guide data analysis and categorize, based on Lazarus and Folkman's theory of transactional coping. Results Four themes emerged from the data analysis: (1) Caregiving Threats. (2) motivations. (3) Responsibility Management. (4) Fear. Conclusion Despite facing significant pressure at work, formal caregivers of elderly inpatients with physical disabilities possess the drive and various coping strategies to excel in their role. Identifying caregivers' experiences of care can be helpful in improving resilience to stress and maintaining stability in formal caregivers.